Uji Toksisitas Akut Herbisida Sintetik Ipa Glifosat Terhadap Mortalitas Benih Ikan Lele Sangkuriang (Clariasgariepinus) - Ita Emilia; Andi Arif Setiawan; Monica Dwi Mutiara (Universitas PGRI Palembang, 2020)
The acute research toxicity test of Ipa Glyphosate herbicide toward mortality of sangkuriang catfish seeds (Clarias gariepinus) as a non target organism. The aim is to decide the concentrate of Ipa Glyphosate herbice that caused 50% mortality of sample (LC50) and the middle time mortality of sample (LT50. The toxicity test had done on March until May 2019 at Integrated Laboratory of PGRI Palembang University. Toxicity test of Ipa Glyphosate herbicide toward mortality of sangkuriang catsfish seeds used bioassay method for 96 hours. Concentrate that used: 29,3%, 34,2%, 39,7%, 45,6%, 52,1%, and 59,3%. The result of this research was got LC50 24 hours was 68,346%, 48 hours was 41,094%, 72 hours was 34,287%, 96 hours was 29,957%, and the result of LT50 for 29,3% concentrate was 79 hours, LT50 for 34,2% concentrate was got 76 hours, LT50 for 39,7% concentrate was got 68 hours, LT50 for 45,6% concentrate was got 42 hours, LT50 for 52,1% concentrate was got 41 hours, and LT50 59,3% concentrate was got 32 hours. Getting lower the concentrate of Ipa Glyphosate herbicide that used, it means more longer time needed to killing the sample.